2016
DOI: 10.1002/app.44203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaO in the thermal crosslinking of maltodextrin and citric acid: A cooperative action of condensation and ionic interactions

Abstract: The study of the effect of CaO in the thermal crosslinking of maltodextrin with citric acid demonstrates that the addition of small amount of this compound enhances the crosslinking of the cured system under processing conditions. This enhancement of the crosslinking leads to a noticeable improvement of the mechanical properties. The mechanism of the enhanced crosslinking reaction has been deeply analyzed by rheology, FT‐IR, and TGA. The rheological results show that CaO contributes to the crosslinking. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…MD is in widespread use because it is nontoxic even when consumed in excessive quantities and is inexpensive. Previous studies have shown that the gelling ability of κ-CRG can be improved by cross-linking CRG with MD [14][15][16]. Hence, we opined that MD is able to modify CRG's structure to reduce the brittleness of the capsules.…”
Section: Introductionmentioning
confidence: 85%
“…MD is in widespread use because it is nontoxic even when consumed in excessive quantities and is inexpensive. Previous studies have shown that the gelling ability of κ-CRG can be improved by cross-linking CRG with MD [14][15][16]. Hence, we opined that MD is able to modify CRG's structure to reduce the brittleness of the capsules.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, when combined with citric acid and after thermal heating, it forms a polymeric network (crosslinking) due to the esterification reaction between the hydroxyl groups of maltodextrin and the carboxyl groups of citric acid (Castro-Cabado, Parra-Ruiz, Casado, & San Román, 2016). In addition to increasing the thermal and mechanical resistance (Castro-Cabado, Casado, & San Román, 2016b), these crosslinking reactions preserve the bioactivity of the encapsulated agents (Francisco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 1616 cm −1 is due to the bound water. The SC, with the addition of citric acid, showed a new peak at 1646 cm −1 compared to unmodified starch S. This peak confirms the formation of carboxyl and ester carbonyl bond formation [ 16 ]. This indicates that citric acid and starch undergo an esterification reaction to form crosslinking bonds.…”
Section: Resultsmentioning
confidence: 89%
“…FTIR analysis was performed in triplicate for samples using an FT-IR spectrophotometer-equipped Spectrum 100 (Thermo Fisher Scientific, Norwalk, CA, USA) with attenuated total reflection (ATR) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%